Animals for Profit: The Ecological and Economic Causes of the War on Coyotes in Kansas from 1890 to 1899 - Spachek, Michael (Kansas State University, The Chapman Center for Rural Studies, 2017)
This study examines how humans, coyotes, and black-tailed jackrabbits interacted under drought conditions in Kansas during the 1890s. Using newspapers, scientific studies, and commissioner’s records from Clay and Riley counties, the study tells the story of desperate people turning to coyote pelts as a source of income. Research from the 1930s and 1950s droughts was used as little research was done during the 1890s. The conditions facilitated an increase of jackrabbits, coyotes, and ultimately, a story of human survival.
Michael Spachek, “Animals for Profit: The Ecological and Economic Causes of the War on Coyotes in Kansas from 1890 to 1899,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/245.
Keywords: Clay Center; Clay County; Coyotes; coyote industry; Grant County; Jackrabbits